Women in Local Politics: A Case Study of Poznań and the Wielkopolska Regional Assembly, 2018–2022 - Kaczmarek, Filip (Wydawnictwo Naukowe Wydziału Nauk Politycznych i Dziennikarstwa UAM, 2024)
The purpose of the study was to examine the participation of women in local government and local politics in the city of Poznań. The study used the method of quantitative analysis that focused on actions taken by female councilors of the City of Poznań and the Wielkopolska Province, including their interpellations and inquiries, and functions held by women in the two local governments. Moreover, the analysis covered political role indicators used in the study by the European Charter on Equality of Women and Men in Local Life. The study considered the period from the beginning of the current local government term (November 2018) to December 31, 2022. It also utilized data published in the Public Information Bulletins of the City of Poznań and the Local Government of the Wielkopolska Province. Celem przeprowadzonego badania było ukazanie udziału kobiet w pracach samorządu terytorialnego i w polityce lokalnej miasta Poznania. Zastosowano metodę analizy ilościowej działań podejmowanych przez radne Miasta Poznania i Województwa Wielkopolskiego, obejmujących interpelacje i zapytania oraz funkcje pełnione przez kobiety w tych dwóch samorządach, a także analizę wskaźników roli politycznej, stosowanych do diagnozy przeprowadzanej na potrzeby Europejskiej Karty Równości Kobiet i Mężczyzn w Życiu Lokalnym. W badaniu uwzględniono okres od początku obecnej kadencji samorządu (listopad 2018 r.) do 31 grudnia 2022 r. Wykorzystano dane publikowane w Biuletynach Informacji Publicznej Miasta Poznania i Samorządu Województwa Wielkopolskiego.
Kobiety w samorządzie terytorialnym i w polityce lokalnej miasta Poznania w latach 2018–2022
Keywords: equality between women and men; local government; local politics; Poznań; Wielkopolska; równość kobiet i mężczyzn; samorząd terytorialny; polityka lokalna